2020
DOI: 10.1080/19476337.2020.1843542
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus coagulans BC198 and Lactobacillus paracasei S38 in combination reduce body fat accumulation and modulate gut microbiota

Abstract: Bacillus coagulans BC198 and Lactobacillus paracasei S38 in combination reduce body fat accumulation and modulate gut microbiota. This study investigated the effects of two single strains (Bacillus coagulans BC198 and Lactobacillus paracasei S38) at a level of 5 × 10 9 CFU and a mixture of these two strains (1 x 10 8 CFU) on body fat accumulation and gut microbiota in rats. In contrast to high-fat control, L. paracasei S38 intakes resulted in significant (p < .05) reductions in total visceral fat (−15%) and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Coculture of Lactobacillus with Bacillus cereus could stimulate the biosynthetic capacities of lactic acid strains [ 33 ]. Combination of Bacillus coagulans BC198 and Lactobacillus paracasei S38 appeared to show greater efficacy in reducing body fat accumulation and modulating gut microbiota than single strains even at a relatively low dose [ 34 ]. Another study reported that the effects of oral administration of Lactobacillus delbrüeckii and Bacillus subtilis combined is better than single on gilthead seabream cellular innate immune responses [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coculture of Lactobacillus with Bacillus cereus could stimulate the biosynthetic capacities of lactic acid strains [ 33 ]. Combination of Bacillus coagulans BC198 and Lactobacillus paracasei S38 appeared to show greater efficacy in reducing body fat accumulation and modulating gut microbiota than single strains even at a relatively low dose [ 34 ]. Another study reported that the effects of oral administration of Lactobacillus delbrüeckii and Bacillus subtilis combined is better than single on gilthead seabream cellular innate immune responses [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota in freshly collected fecal samples from each rat was analyzed by 16S rRNA gene sequencing and bioinformatics analysis based on the methods described by Hsieh et al [18]. Fecal DNA was first extracted with the CatchGene TM Stool DNA kit (CatchGene Co., Ltd., Taipei, Taiwan) by following the manufacturer's protocol.…”
Section: Analysis Of Gut Microbiotamentioning
confidence: 99%